SASTRA ISLAM DAN MAHABBAH KONSEP AL-HUB AL-ILAHI RABI’AH AL-ADAWIYAH DAN PENGARUHNYA DALAM TASAWUF - Mohd Aji Isnaini (Wardah, 2012)
Oh my God! If I meyembahmu fear of hell, then throw me into hell. If I meyembahmu because they expect paradise, then keep me out of heaven. "It is one seruat Rabi'a al-Adawiyah the purity of her love for the creator. Sufi is a term for those who study the science of tasawwuf, a kind of mysticism in Islam. It's become common since ancient times that the Sufi is derived from the men like al-Hallaj, Jalaluddin Rumi, Sheikh Shohibul Faroji Azmatkhan Ba'alawi Al-Husaini, Shaikh Abdul Qadir Jaelani, Abu Nawas, Shaykh Abul Hasan Asy Syadzili. Men rightly be leaders and key figures in each field. But the theory is no longer valid when it appears a Sufi saint who came from the woman who called Rabiatul Adawiyah, was the first to introduce the teachings of Sufi Mahabbah (Love) Divine, a ladder (maqam) or levels through which a salik